Interstitial hernia: A diagnostic dilemma in infants and children - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 1998)
The features of the rare interstitial hernia, as seen in four children, are described. All were boys ranging in age from 7 days to 7 years. The presenting sign was swelling in the right side of the abdomen associated with undescended testis. The hernias arose at the deep inguinal ring and expanded superiorly between the internal and external oblique muscles. Repair involved a standard herniotomy and orchidopexy through an oblique inguinal incision-except in one patient with a vanishing testis. The importance of being aware of this rare type of hernia is stressed. Copyright (C) 1998 by W.B. Saunders Company.
Keywords: interstitial hernia; interparietal hernia; inguinal hernia; undescended testis